The effect of e-service quality and perceived risk on customer loyalty among Bangladeshi online banking consumers - Uddin, Bashir; Maulan, Suharni; Mitro, Happy; Al Mamun, Mohammad Abdullah (Pacific Academy of Higher Education & Research University, 2024)
Purpose: This quantitative study aims to determine the impact of two variables-online banking service and its perceived threat—on consumer pleasure and purchaser loyalty in Bangladesh. Methodology: Of late, a survey was conducted to gather primary data, and a total of 329 respondents were selected using a convenient specimen approach from a specific group of public and authority-owned banks. Although the right devices have been chosen for each construct by experimental review, the relationship between some of the constructs has been carefully assessed through the use of structural modeling. Factor analysis systems have been employed to perceive the underlying structures and a few of the explored online banking service attributes. Findings: The results of an exploratory issue evaluation revealed twelve composite dimensions of first-class electronic service and perceived threat, which included the availability of convenient electronic banking operations. The structural modeling method was used to assess the relationships between some of the constructs, and exploratory analysis was carefully employed to determine the right items for each construct. It appears from their examination that there are clear connections between buyer satisfaction, client loyalty, and perceived hazards. Research Limitations: Generally, relating to only employer awareness, exploratory thing analysis is employed, and an alternative generalized view of digital banking is adopted. Future research needs the intention to improve on these by replicating the examination in multi-industry settings, assessing the stability of the revealed issue shape, and examining whether specific e-providers great and perceived threat factors range in significance across one of the generations or not. Originality/Value: This study used a sample of 329 online banking customers in Bangladesh to investigate the key elements of the relatively new electronic service satisfaction assembly and assess the survey participants' perceptions of the risk associated with online banks'